G175 A shared outcome perinatal mental health value scorecard to support health visitors to improve outcomes for children 0–5 years and their families. (27th April 2016) - Lakhanpaul, M; Irish, C; Jarvis, R; Edbrooke-Childs, J; Deighton, J; Franklin, M; Hunter, R; Gleeson, H
Abstract : Aim: Perinatal mental health problems affect at least 10 per cent of women but can impact on the child. We developed a value scorecard and demonstrated how it could be utilised as a quality improvement tool to mediate the mental health of mothers and their families to improve long-term outcomes of children 0–5 years. Method: Our value scorecard was co-designed with parents, commissioners, health visitors and other clinical experts to develop a set of outcome measures that matter most to parents and deliver outcomes that are meaningful to all stakeholders. It was piloted across four provider sites in London by collecting data to populate and test the feasibility of the score card. Evaluation methods: Multi-level, mixed methods realistic evaluation Change in collecting routine clinical data from the scorecard including patient reported experience measure (PREM) 34 questionnaires on HV knowledge, confidence and skills regarding perinatal wellbeing, the Scorecard and QI Focus groups with 23 mothers Interviews/focus groups with 41 HVs Random case note audit and case studies of QI projects. Results: We demonstrated a trend in increase over time of adherence of use of the maternal mood assessments following introduction of score card. The economic modelling demonstrated that the implementation of the scorecard appeared to reduce costs (£3, 357) and increase in QALYs (0.1 to 0.4) Cost-effectiveness of screening for peri-natal depression with necessary follow-up or onward referral post-implementation of the scorecard vs. pre-implementation Significant increase in screening for both antenatal and postnatal depression and it was shown to be cost-effective in the modelled cost-effectiveness analysis Conclusion: Our perinatal mental health scorecard used in one site showed a significant increase in screening for both antenatal and postnatal depression and was shown to be cost-effective in the modelled cost-effectiveness analysis. These results should be considered exploratory based on the implementation of the scorecard as part of a pilot study – further analysis with a larger quantity and better quality data in relation to the perinatal mental health scorecard is required.